Representações da leitura: uma análise discursiva do que dizem ingressantes e formandos de cursos de Letras sobre essa prática - Zaccaro, Renata Maria Cortez da Rocha (Universidade Federal de São Carlos, 2019)
The objective of this research was to investigate representations of reading shared by both Literature and Language undergraduate students in the first year and in the last academic year in college. The observation intended to infer possible similarities and differences related to how they create, express and perform reading practices in the first and in the last year of college. In order to accomplish this observation, a data survey was performed among Literature and Language college students from the first and the last semesters, from both a private college and a state college. They responded to a questionnaire containing objective and open-ended questions that aimed to encourage them to describe their reading perceptions, habits, and preferences and their own way of reading before getting into college and throughout the academic training. Principles and concepts of the French Discourse Analysis, especially those from Michael Foucault’s “order of discourse” form the theoretical and methodological basis for this research. In order to understand what is on the basis of what the students express about their discourse, this research is also based on the Cultural History, especially on Roger Chartier’s practices of writing and reading. Some of the responses given by the Literature and Language students on the questionnaire are shown in tables and figures in order to present from a quantitative point of view some of thoughts that they share about reading. Some statements that the students registered on the open-ended questions were selected to organize formally and informally rephrased groups of answers in order to understand their connections to certain discourses about reading that were originated or not from the same discursive background and that correspond to a given updated discursive memory and its many diverse forms of institutionalization and length over time. This study therefore described the conditions of production according to which these discourses were shaped by what the Literature and Language undergraduate students who are being trained to become reading instructors, among other possibilities, express.
Representations of reading: a discourse analysis about what Literature and Language undergraduate students in the first year and in the last academic year in college say about their practices
Keywords: Leitura; Análise do discurso; História cultural; Alunos de Letras; Reading; Discourse analysis; Cultural history; Literature and Language undergraduate students; LINGUISTICA, LETRAS E ARTES::LINGUISTICA